Pengaruh Differensiasi Produk dan Kualitas Pelayanan terhadap Keputusan Pembelian Makanan Cepat Saji Richeese Factory Rempoa - Danawira, Ardha (Jurnal Ilmu Manajemen, 2019)
The culinary industry is mushrooming along with the busyness of the community and its high mobility. One such industry is fast food. Competition in the fast food industry is also growing fast so differentiation is needed to win the competition. This research discusses the difference between product and service quality with the decision to buy fast food Richeeese Factory Rempoa, South Jakarta. In this study a sample of 133 fast food respondents was used in Rempoa, South Jakarta. This study uses a survey method by collecting data directly, which is derived from a questionnaire distributed to the sample. Sampling uses non-probability sampling with accidental sampling method. The results of the study prove that there is an effect of differentiation and product quality both simultaneously and partially on the decision to purchase fast food from Richeese Factory, Rempoa, South Jakarta.